Lessons learned and policy implications from climate-related planned relocation in Fiji and Australia - Piggott-McKellar, Annah; Vella, Karen (Frontiers in Climate, 2023)
Planned Relocation is a form of mobility in response to climate-related shocks and slow onset change. While the primary focus of the seminal Foresight report on Migration and Environmental Change dealt with mobility processes of migration and displacement, planned relocation was discussed as a viable, yet fraught adaptation strategy. Since the publication of the Foresight report in 2011, considerable research into planned relocation has progressed understanding, in part due to the emerging case study examples globally over the last ten years. The authors of this article have undertaken research in communities across Australia and Fiji who have initiated and undertaken planned relocation processes, to varying degrees of completion and success. As part of the Research Topic - Climate Migration Research and Policy Connections: Progress Since the Foresight Report - in this article we look back at the lessons that emerged from the Foresight report, and provide key insights from our experiences, as well as through drawing on the broader literature, and through doing so offer lessons learned, and policy insights for planned relocation across these regions, and beyond. This research is especially relevant given the context of planned relocation in these two nations: Australia, a country that has experienced severe fires and flooding events over the last few years, which have raised important questions around the role planned relocation may play in future national adaptation discussions and planning, with buy-back schemes occurring across the country; and Fiji, a country at the forefront of planned relocation globally, with 800 communities listed as in need of relocation by the Government of Fiji, and numerous cases of completed, initiated and planned relocation emerging. Primary findings indicate: there are examples of people choosing to remain in sites of exposure despite relocation plans, making the notion of ‘voluntariness’ essential; relocation has the potential to be a successful adaptation option if planned well with strong participatory governance; a need to think broadly and holistically around the needs and livelihoods of effected communities in relocation planning; and the need for longitudinal studies to track the implications and impacts (positive and negative) of relocation in the long term.